Endoscopic submucosal dissection for nonampullary large superficial adenocarcinoma/adenoma of the duodenum: feasibility and long-term outcomes - Hoteya, Shu; Yahagi, Naohisa; Iizuka, Toshiro; Kikuchi, Daisuke; Mitani, Toshifumi; Matsui, Akira; Ogawa, Osamu; Yamashita, Satoshi; Furuhata, Tsukasa; Yamada, Akihiro; Kimura, Ryusuke; Nomura, Kosuke; Kuribayashi, Yasutaka; Kaise, Mitsuru (Endoscopy International Open, 2013)
Background and study aims: The clinical benefit of endoscopic submucosal dissection (ESD) for superficial duodenal neoplasias has not yet been verified. The aims of this study were to validate the feasibility and long-term outcomes of ESD for nonampullary superficial duodenal neoplasias, larger than 20 mm.Patients and methods: 41 patients, with 41 nonampullary large superficial duodenal neoplasias, who underwent ESD between April 2005 to March 2013 were included in the study. The short- and long-term outcomes were retrospectively evaluated, related to tumor size, resection size, histological type, invasion depth, complete resection rate, operation time, perforation rate, delayed bleeding rate, local recurrence rate, distant metastasis, and survival rate.Results: ESD was successfully completed in 38 of 41 patients (92.7 %). The median sizes of tumors and resected specimens were, respectively, 26 mm (range 20 – 70 mm) and 36.5 mm (range 23 – 80 mm). Histopathological findings showed 13 adenocarcinomas (12 mucosal, 1 submucosal) and 28 adenomas (26 high grade dysplasia, 2 low grade dysplasia). The complete resection rate was 89.5 % (34 /38 tumors). The mean operation time was 128.3minutes. Perforation during ESD occurred in 39 % and delayed bleeding occurred in 18.4 %. The median observation period was 48 months (range 3.2 – 94.1 months), and no local recurrence or distant metastasis was seen during this time, representing a disease-free survival rate of 100 %.Conclusions: ESD for nonampullary large superficial duodenal adenocarcinoma/adenoma is feasible with favorable long-term outcomes. However, because of the high complication rate due to its technical difficulty, experience and skill of the operator, along with adequate perioperative management, are essential.